Structural factors controlling size reduction of graphene oxide in liquid processing - Nacken, Thomas; Halbig, Christian E.; Wawra, Simon; Damm, Cornelia; Romeis, Stefan; Walter, Johannes; Tehrani, Mohammad J.; Hu, Yichen; Ishii, Yoshitaka; Eigler, Siegfried; Peukert, Wolfgang (Carbon, 2017)
Graphene oxide materials can be prepared in manifold synthesis approaches and allow for further post-functionalization to adopt the properties of the desired application. Small sized sheets with lateral dimensions on the 100 nm scale are e.g. beneficial for cell applications. Breakage of sheets by liquid phase processing is an ideal way to generate such nano-sized sheets. However, until now it is unknown how functionalization influences the breakage behavior. We have chosen single layered oxo-functionalized graphene (oxo-G) derivatives with lattice defects < 1% to evaluate their size reduction rate upon ultrasonication of flakes with respect to the type and degree of functionalization of the graphene sheets. Lateral dimensions of the processed sheets were quantitatively determined in solution by analytical ultracentrifugation. The highest size reduction rate is observed for pristine oxo-G, which bears the highest degree of functionalization of around 60% and the negatively charged organosulfate group. Partial hydrolysis of organosulfate, or conversion of surface-functional groups to hydroxyl-groups in majority or partial defunctionalization lead to size-reduction rates which are up to 25% lower in comparison with the initial oxo-G. Moreover, the size reduction rate can be correlated in first approximation also with UV–vis spectroscopy.